2013
DOI: 10.2744/ccb-1037.1
|View full text |Cite
|
Sign up to set email alerts
|

Sex in the Half-Shell: A Review of the Functions and Evolution of Courtship Behavior in Freshwater Turtles

Abstract: ABSTRACT. -Freshwater turtle courtship is an exciting and potentially phylogenetically important field of study. Scattered data exist from the past century of research, yet no recent summary is available. Courtship in freshwater turtles includes a number of common behaviors, which usually involve visual, tactile, olfactory, and auditory signals. These signals function in both species and sex recognition and in the seduction of potential mates. Specific behavioral sequences are required to facilitate successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…Organisms with long life spans, overlapping generations, and promiscuous mating systems violate some of these assumptions (Frankham et al 2002) and may therefore experience the genetic effects of population fragmentation and decline differently. For example, most species of turtle have delayed maturity, long generation times (often >25 years), long life spans, and polygamous or promiscuous mating systems (Congdon et al 1993(Congdon et al , 1994Litzgus 2006;Davy et al 2011;Liu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Organisms with long life spans, overlapping generations, and promiscuous mating systems violate some of these assumptions (Frankham et al 2002) and may therefore experience the genetic effects of population fragmentation and decline differently. For example, most species of turtle have delayed maturity, long generation times (often >25 years), long life spans, and polygamous or promiscuous mating systems (Congdon et al 1993(Congdon et al , 1994Litzgus 2006;Davy et al 2011;Liu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Reptiles have featured prominently in research on sexual dimorphism because of their high degree of variation in dimorphisms and life histories (Cox et al 2008). Both male-and femalebiased sexual size dimorphisms are well recorded in Testudines and have been related to male mating strategies, female fecundity, ecological selection, and phylogenetic patterns (Berry and Shine 1980;Shine 1989;Stephens and Wiens 2009;Ceballos et al 2013;Liu et al 2013). Turtles of the family Emydidae are a model group in the study of sexual dimorphism owing to their taxonomic and ecological diversity (Stephens and Wiens 2003), relatively thorough study (Lovich and Ennen 2013), and range of interesting sexual dimorphisms, including some of the most head, elongate snout, and angular rostrum (Boycott and Bourquin 2000;V.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been suggested that some of the colourful regions found particularly in males may potentially be involved in intersexual communication and mate choice [35,40]. In freshwater turtles courtship takes place underwater and males adopt characteristic positions relative to the female [41]. Deirocheline turtles are characterized by elaborated courtship behaviour including a complex forelimb display known as titillation [41].…”
Section: Introductionmentioning
confidence: 99%
“…In freshwater turtles courtship takes place underwater and males adopt characteristic positions relative to the female [41]. Deirocheline turtles are characterized by elaborated courtship behaviour including a complex forelimb display known as titillation [41]. Males in most species of deirocheline turtles perform the titillation display facing the female while swimming backwards in front of her, mostly near the surface; however, males of the genus Pseudemys titillate swimming above and parallel to the female, facing the same direction as her [41–46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation